Innovative approach to sustainable development of green economy in Uzbekistan - Xalilova Maftuna Raxmon qizi; Bahromova Dilnavoz Azamat qizi (THE INNOVATION ECONOMY, 2026)
This article examines the role and significance of innovative approaches in the sustainable development of the green economy in Uzbekistan. The conceptual foundations of the green economy, the balance between environmental sustainability and economic growth, and the effective use of resources through the implementation of modern technologies are analyzed. Furthermore, the article reviews national strategies, legislative frameworks, and practical programs adopted by the Government of the Republic of Uzbekistan in the field of green development, emphasizing the role of innovation in their implementation. The study discusses the potential of clean technologies, investments in renewable energy sources, digital solutions, and green finance mechanisms in diversifying the econ omy. The research concludes by highlighting the necessity of integrating science and innovation in advancing the green economy and proposes promising directions for its further development.